Synergy of antithrombin III concentrate and antivenom in preventing coagulopathy in a rat model of Malayan pit viper envenoming. - Pukrittayakamee, S; Desakorn, V; Clemens, R; Nontprasert, A; Bock, H; White, N; Bunnag, D (1990)
The effects of unrefined equine antivenom and antithrombin III (AT-III) concentrate on the coagulopathy induced by systemic envenomation by Malayan pit viper (Calloselasma rhodostoma; MPV) venom were investigated in a rat model. 37 rats received an intramuscular injection of MPV venom and serial blood samples were taken from the femoral vein for simple whole blood clotting tests and measurement of AT-III activity. 30 min after venom injection, treatment (antivenom, AT-III or both) was given intravenously. 6 rats were untreated and all developed uncoagulable blood and AT-III depletion 90-210 (median 180) min after venom injection. A combination of high dose AT-III concentrate (0.5 units/g) and antivenom (20 micrograms/g) prevented abnormal clotting (P less than 0.001), whereas AT-III alone, antivenom alone, or a combination of low dose AT-III (0.25 units/g) and antivenom did not (P less than 0.05). These results suggest that the coagulation abnormality in MPV envenomation is secondary to activation of the coagulation cascade at several levels, and that treatment with antivenom alone may not be sufficient to reverse or prevent this phenomenon.